A direct translaminar inhibitory circuit tunes cortical output - Pluta, Scott (Nat Neurosci, 2015)
Anatomical and physiological experiments have outlined a blueprint for the feed-forward flow of activity in cortical circuits: signals are thought to propagate primarily from the middle cortical layer, L4, up to L2/3, and down to the major cortical output layer, L5. Pharmacological manipulations, however, have contested this model and suggested that L4 may not be critical for sensory responses of neurons in either superficial or deep layers. To address these conflicting models we reversibly manipulated L4 activity in awake, behaving mice using cell-type specific optogenetics. In contrast to both prevailing models, we show that activity in L4 directly suppresses L5, in part by activating deep, fast spiking inhibitory neurons. Our data suggest that the net impact of L4 activity is to sharpen the spatial representations of L5 neurons. Thus we establish a novel translaminar inhibitory circuit in the sensory cortex that acts to enhance the feature selectivity of cortical output.